High-performance composite with negative Poisson’s ratio - Steffens, Fernanda (2017)
This article presents innovative work undertaken to evaluate the auxetic composite materials developed using weft-knitted fabrics with negative Poisson’s ratio (NPR) produced from high-tenacity filaments of para-aramid (p-AR) and polyamide. The aim of this study is to develop polymeric composite materials reinforced with auxetic knitted fabrics and to evaluate the degree of transference of the auxetic behavior from the fibrous reinforcement to the composite produced. The results show that the NPR values remained in the composites. Regardless of the type of resin used, either epoxy or polyester, the highest values were obtained for samples produced with p-AR auxetic knitted fabrics. The NPR composites developed within this work present great potential for applications in industrial areas, including personal protection products, such as bulletproof vests, helmets, knee, and elbow protectors, and in all other areas where energy absorption is a key factor to be considered.